Answer:
C
Step-by-step explanation:
You were right about C, so there's no need to worry about it
Answer: d.h=−4
PLZ MARK BRAINLIEST!
Step-by-step explanation:
Let's solve your equation step-by-step.
−3(h+5)+2=4(h+6)−9
Step 1: Simplify both sides of the equation.
−3(h+5)+2=4(h+6)−9
(−3)(h)+(−3)(5)+2=(4)(h)+(4)(6)+−9(Distribute)
−3h+−15+2=4h+24+−9
(−3h)+(−15+2)=(4h)+(24+−9)(Combine Like Terms)
−3h+−13=4h+15
−3h−13=4h+15
Step 2: Subtract 4h from both sides.
−3h−13−4h=4h+15−4h
−7h−13=15
Step 3: Add 13 to both sides.
−7h−13+13=15+13
−7h=28
Step 4: Divide both sides by -7.
−7h
−7
=
28
−7
h=−4
First convert from standard to slope intercept form.
3x+4y=12
4y=-3x+12
y=-3/4x+3
The slope should be -3/4 and the y intercept should be 3.
Final answer: D